Peningkatan Hasil Belajar Siswa pada Materi Pecahan Senilai Menggunakan Model Project Based Learning (PjBL) - Fitria, Mila; Zainil, Melva (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study aims to improve the learning outcomes of fractions worth using the Project Based Learning (PjBL) model in class IV SDN 17 Sungai Pandahan Pasaman Regency. This type of research is classroom action research using qualitative and quantitative approaches. Subjects in this study were 21st grade students of SDN 17 Sungai Pandahan Pasaman Regency, with a total of 21 people, consisting of 11 men and 10 women. The research instrument used test sheets, non-tests and observations and the data analysis techniques used were descriptive qualitative and quantitative. The results showed that by using the Project Based Learning (PjBL) model could improve student learning outcomes in fractions worth material.